Correlação entre o índice cardiofemoral e o déficit de hemoglobina em fetos de gestantes isoimunizadas - Tatiana Saber de Andrade (2007)
Introduction: fetal anemia resulting from isoimmunized pregnant women has caused great interest due to its morbimortality and to its still high prevalence in our society. For an adequate follow-up and treatment of the hemolytic disease, it is necessary a precise diagnosis of the degree of the fetal anemia. In spite of the efficacy of the amniocentesis and cordocentesis for the pre-natal follow-up in isoimmunized pregnant women, the complications associated to these procedures justify the search for non-invasive diagnosis methods, which may safely predict the intensity of the fetal anemia. The biventricular outer dimension/femurlength index has been used as an important non-invasive evaluation method for fetal anemia, however further studies are still required, in order to validate its scientific value. Purpose: to evaluate the correlation between the ultrasound measurement of the biventricular outer dimension/femur length index and the hemoglobin deficit in isoimmunized pregnant womens fetus. Patients and methods: it is a transversal study in which 125 fetuses have been followed up with a gestational age ranging from 20 to 35 weeks, of 124 women with redblood cells isoimmunization, whose fetuses showed risks of a significant anemia, therefore with indication for a cordocentesis. Before this procedure, with the 4-chamber ultrasound views of the fetal heart in real time and with the M-mode, was carried out the measurement ofthe outer left ventricular diameter, followed by the measurement of the femur length, located along the diaphysis, being excluded the distal epiphysis. Starting from such measurements, the biventricular outer dimension/femur length index was determined. The ultrasoundequipment used was a US SONOACE 8800 (MEDSOM), with a 3.5 MHz sectorial drill. The hemoglobin concentration was determined by means of a photometer in the HEMOCUE system. The hemoglobin deficit was calculated based on Nicolaides normality curve (NICOLAIDES et al., 1988a). Based on such deficit was prepared a classification of theanemia degree. Absence of anemia was defined when the hemoglobin deficit was < 2 g/dl; non-serious anemia when the hemoglobin deficit was = 2gdl, and < 5 mg/dl; and serious anemia when the hemoglobin deficit was = 5mg/dl. Results: The 124 isoimmunized pregnant women were submitted to measurement of the biventricular outer dimension/femur length index, followed by cordocentesis, totaling 339 cases for analysis. At the time of inclusion in the study, 24% of the 125 fetuses did not present anemia, in 40.8% it was classified as notcritical and in 35% it was considered as serious. The biventricular outer dimension/femur length index figures were in average significantly lower in the group without serious anemia and higher in the group with serious anemia (p<0.05). A significant and positive correlation was observed between the biventricular outer dimension/femur length index and thehemoglobin deficit (r= 0.344 and p<0.001). The 0.60 value was considered as the best cutting point for said index, being noticed a balance between sensitivity and specificity. For detecting the serious fetal anemia, considering as cutting point the 0.60 biventricular outerdimension/femur length index, the sensitivity and specificity found were respectively 85.3% and 58.7%. Conclusion: in isoimmunized pregnant womens fetuses, the biventricular outer dimension/femur length index is directly related to the hemoglobin deficit. Such finding suggests that these measures may be used as a non-invasive diagnosis method for fetal anemia in these pregnant women.